On the Path to Decolonizing Health Care Services: The Role of Marketing - Gaurangi Laud; Steven D’Alessandro; George Reece; Mehmet Mehmet Ibrahim; Mona Nikidehaghani; Michelle Evans; Deirdre Tedmanson (2023)
Despite considerable investment, health outcomes for First Nations people are well below those of the rest of the population in several countries, including Canada, the USA, and Australia. In this paper, we draw on actor-network theory and the case of “Birthing on Country,” a successful policy initiative led by First Nations Australians, to explore the decolonization of health services. Using publicly available archival data and the theoretical guidance of actor-network theory, our analysis offers insight into how marketing techniques and technologies can be deployed to achieve improved health outcomes and implement decolonial approaches. The insights provided have theoretical implications for marketing scholarship, social implications for understanding and implementing an agenda of decolonization, and practical implications for healthcare marketing.